Active commuting and the health of workers - Echeverría, Lucía (2023)
Introduction: Research has shown that commuting is related to the health of workers, and that mode choice may have a range of effects on this relationship. We analyze the relationship between active commuting (walking and cycling) and the health status reported by US workers. Methods: We use the 2014–2016 Eating and Health (EH) Module of the American Time Use Survey (ATUS). We estimate Ordinary Least Squares models on a measure of subjective health that is the self-reported assessment of individual general health status, and on the body mass index. Results: longer commutes by bicycle are significantly related to higher levels of subjective health and to lower body mass index, while commuting by walking is only weakly related to both health measures. We test the robustness of our results to possible measurement error in commuting times, to the exclusion of compensating factors, to the estimation method, and to the inclusion of time devoted to leisure-based physical activities. Conclusions: Our results may help policy makers in evaluating the importance of infrastructures that facilitate the use of bicycles as a means of transport, boosting investment in these infrastructures, especially in larger cities.